Clinical Nutrition and Health: Diagnosis, Therapy, and Disease Prevention - Siti Nur Avira; Dewi Anjani Imha Putri (Professorline, 2026)
Clinical nutrition plays a central role in the prevention, diagnosis, and management of nutrition-related diseases such as diabetes, obesity, anemia, cardiovascular disorders, and malnutrition. In recent decades, the increasing prevalence of non-communicable diseases has highlighted the importance of nutrition as both a preventive and therapeutic tool in healthcare systems. This paper examines the fundamental principles of clinical nutrition, focusing on its application in disease diagnosis, dietary intervention, and long-term health maintenance. A qualitative literature review was conducted using peer-reviewed scientific articles, international health organization reports, and clinical guidelines related to medical nutrition therapy. The findings indicate that personalized nutrition interventions significantly improve patient outcomes, reduce disease complications, and enhance overall quality of life. Moreover, interdisciplinary collaboration among dietitians, physicians, and public health professionals is essential for effective implementation of clinical nutrition strategies. This study concludes that integrating clinical nutrition into mainstream healthcare is crucial for reducing the global burden of nutrition-related diseases and promoting sustainable health systems.